1990
DOI: 10.1209/0295-5075/13/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Matter Distribution in Neutron-Rich Light Nuclei and Total Reaction Cross-Section

Abstract: Mean square radii of light radioactive projectiles, including exotic isotopes close to the neutron drip line ("Li, 14Be, and 17B), have been deduced from total reaction cross-section measurements, using a simple microscopic model. The isospin dependence of nuclear radii is discussed and compared to other experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 14 publications
9
84
0
Order By: Relevance
“…The extracted rms radius of 11 C is quite small though in agreement with high energy data [19]. An independent measurement by Liatard et al [37] indicates a much larger value, 2.46±0.30 fm, in agreement with our HF calculation of 2.48 fm (see Table III). …”
Section: Discussion Of Resultssupporting
confidence: 89%
“…The extracted rms radius of 11 C is quite small though in agreement with high energy data [19]. An independent measurement by Liatard et al [37] indicates a much larger value, 2.46±0.30 fm, in agreement with our HF calculation of 2.48 fm (see Table III). …”
Section: Discussion Of Resultssupporting
confidence: 89%
“…[43], 2.38 ± 0.01 fm, obtained with Glauber-model calculations from interaction cross sections at high ener- gies. A different estimation from a simple microscopic model by using cross sections at intermediate energies gives a radius of 2.53 ± 0.07 fm [44], in better agreement with our calculation. It has been pointed out [45] that the optical limit approximation of Glauber models, such as in Ref.…”
Section: B 3/2supporting
confidence: 88%
“…On the other hand, measurements of the interaction cross sections at relativistic energies for particlestable B isotopes ranging from mass 8-15, by Tanihata, et al [22], suggested that their effective RMS radii are practically constant, which does not support the halo hypothesis. Measurements at intermediate energy, analyzed by Liatard, et al [23], gave larger RMS radii in all cases than those of Ref. [22], together with a significant mass dependence and an anomalously large radius for 14 B.…”
Section: Neutron Halo Inmentioning
confidence: 56%